2012
DOI: 10.1097/nmd.0b013e31824cb359
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairments in Schizophrenia and Schizoaffective Disorder

Abstract: The present study aimed to compare population-based familial samples of patients with schizophrenia (n = 218) and schizoaffective disorder (n = 62) and a healthy control group (n = 123). Patients with schizoaffective disorder outperformed patients with schizophrenia in verbal ability, processing speed, visual working memory, and verbal memory. When compared with controls, patients with schizoaffective disorder also had a generalized cognitive impairment. Adjusting for clinical characteristics removed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…However, naturalistic, cross-sectional studies have suggested that higher doses of antipsychotics (Élie et al, 2010, Hori et al, 2006, Torniainen et al, 2012) or antipsychotic polypharmacy (Hori et al, 2006) may be associated with poorer cognitive functioning in schizophrenia, supported also by the finding of a positive effect of dose-reduction on cognition (Kawai et al, 2006, Takeuchi et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…However, naturalistic, cross-sectional studies have suggested that higher doses of antipsychotics (Élie et al, 2010, Hori et al, 2006, Torniainen et al, 2012) or antipsychotic polypharmacy (Hori et al, 2006) may be associated with poorer cognitive functioning in schizophrenia, supported also by the finding of a positive effect of dose-reduction on cognition (Kawai et al, 2006, Takeuchi et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cognitive impairment associated with preand postmorbid SZ (Srensen et al, 2006;Goff et al, 2011) is a clinical feature that has been associated with psychosis duration (Simonsen et al, 2011) as well as negative symptoms (Lewandowski et al, 2011). A recent evaluation of cognitive performance between SZ and schizoaffective disorder indicate that schizoaffective disorder patients have severe cognitive impairments, but these impairments are milder than those in SZ patients (Torniainen et al, 2012). At the same time, a recent assessment of SZ and BP+ probands showed little, if any, differences in altered cognitive performance between groups using standardized clinical and neuropsychological measures (Ivleva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cognitive differences have been documented in multiples studies in younger adults with serious mental illness. 4,912 It is possible that differences in cognitive functioning tend to abate with time as adults with serious mental illness experience age-related cognitive decline. The lack of differences in cognitive functioning across diagnoses may also be explained by our study criteria that excluded participants with Mini-Mental Status Examination scores less than 20.…”
Section: Discussionmentioning
confidence: 99%
“…5–7 Dating back to Pope and Lipinski’s seminal paper suggesting that schizoaffective disorder reflects “good prognosis schizophrenia”, 8 research has found that schizoaffective disorder is associated with better long-term functional outcomes and cognitive functioning compared with schizophrenia. 4,912 Research on the clinical characteristics of schizoaffective disorder has generally suggested that these individuals have less cognitive impairment than adults with schizophrenia but possibly more than individuals with bipolar disorder. 6,9,12 Other studies have suggested that schizoaffective disorder is associated with higher occupational functioning, more social contact, higher quality of life, more insight into the disorder, and are healthier overall than individuals with schizophrenia; 4,5,10,13 nevertheless, individuals with schizoaffective disorder tend to be hospitalized more frequently.…”
mentioning
confidence: 99%
See 1 more Smart Citation